Medical students impacted by discrimination: a qualitative study into their experiences of belonging and support systems at medical schools in the UK - Megan E L Brown; Sonia Kumar; Ravi Parekh; Victoria Collin; Hamza Ikhlaq; Srishti Agarwal; Catharine Kwok; Hadiya Golamgouse; Simone Derby; Nicola McRae (BMJ Open)
Objective To better understand the broader experience of medical students impacted by discrimination and the support systems they engage with.Design Qualitative study using semi-structured interviews.Setting Four medical schools based in the UK.Participants 17 medical students were recruited using volunteer and snowball sampling: all students self-identified as being impacted by discrimination.Results 5 themes were identified: feelings of isolation, imposter syndrome and exclusion; a lack of representation and positive role modelling; the importance of peer support; issues relating to the accessibility of support; building support networks through shared experiences and attempts to foster a sense of inclusion through peer and institutionally led initiatives.Conclusions The findings of this study suggest medical schools could do more to recognise the importance of acknowledging the multiple identities at risk of discrimination held by students, perpetuating feelings of isolation and exclusion. Our research highlights the need for practical systemic initiatives to improve the sense of belonging of medical students who are impacted by discrimination. Medical educators and institutions should consider formal and informal provisions, such as creating time and space for students to meet and share experiences, access support and reporting networks, to foster a greater sense of belonging.